Food and industrial bioproducts and bioprocessing - Dunford, Nurhan Turgut , 1953- (Wiley-Blackwell, 2012)
Food and Industrial Bioproducts and Bioprocessing describes the engineering aspects of bioprocessing, including advanced food processing techniques and bioproduct development. The main focus of the book is on food applications, while numerous industrial applications are highlighted as well